Ulama dan Institusi Pendidikan Islam - Akramunisa, Akramunisa (Al-Riwayah : Jurnal Kependidikan, 2017)
Islamic Scholars (Ulama) occupy a very important place in Islam and in the Muslims’ lives. Islamic scholars institutional environment is actually something strange thing, it was given a prophetic traditions explained that no ecclesiastical institution in Islam. Of course, the difference of teaching institutes with ecclesiastical institutions. Conceptually, the ecclesiastical institution does not exist in Islam, because Islam teaches everyone a direct relationship with God, without intermediaries. A cleric is not a professional representative of God, who was appointed and paid therefore be dismissed. Teaching institutes do not exist, although many recognized the community as religious scholars and jurists (lawyers or judges). The new teaching institutes arise a later as a result of social processes and they are called as scholars rather than scientist of tafsir, hadith experts, and legal experts, who writes books or teaching, but who researched and developed the science. A point to be noted, that in the Middle Ages there has been no real statement among the scholars who work as teachers and scholars who are not working as a teacher, because everyone learned that both salaried or not both trying to give lessons on society.